Loneliness but Narcissistic! - Mely Muliati; Nurul Aiyuda; Itto Nesyia Nasution (Jurnal Riset Psikologi, 2022)
Abstract. The most popular social media today is Tiktok. One of the users of Tiktok is a teenager. Teenage Tiktok users will tend to upload photos or videos excessively to get attention and praise from others which lead to narcissistic tendencies. Narcissistic tendencies are feelings of excessive love and concern for oneself. One of the factors that influence narcissistic tendencies is loneliness. The purpose of this study was to determine the relationship between loneliness and narcissistic tendencies among adolescent Tiktok users in Pekanbaru. This research uses the correlational quantitative method. The subjects in this study were 349 respondents, namely 100 males and 249 females aged 12-21 years who were Tiktok users in Pekanbaru. The sampling technique uses quota samples and sampling uses the provisions of Isaac and Michael's table. Method of data analysis using simple regression test. The results of this study indicate that there is a relationship between loneliness and narcissistic tendencies in adolescent Tiktok users in Pekanbaru, thus the hypothesis in this study is accepted. Abstrak. Media sosial yang paling digemari saat ini ialah Tiktok. Salah satu pengguna Tiktok ialah remaja. Remaja pengguna Tiktok akan cenderung mengunggah foto ataupun video secara berlebihan untuk mendapatkan perhatian dan pujian dari orang lain yang mengarah pada kecenderungan narsistik. Kecenderungan narsistik merupakan rasa cinta dan perhatian yang berlebihan pada diri sendiri. Salah satu faktor yang mempengaruhi kecenderungan narsistik ialah kesepian. Tujuan penelitian ini adalah untuk mengetahui hubungan kesepian terhadap kecenderungan narsistik pada remaja pengguna Tiktok di Pekanbaru. Penelitian ini menggunakan metode kuantitatif korelasional. Subjek dalam penelitian ini sebanyak 349 responden yakni 100 laki-laki dan 249 perempuan berusia 12-21 tahun merupakan remaja pengguna Tiktok di Pekanbaru. Teknik pengambilan sampel menggunakan sampel kuota dan penarikan sampel menggunakan tabel Isaac dan Michael. Metode analisa data menggunakan uji regresi sederhana. Hasil dalam penelitian ini menunjukan adanya hubungan kesepian terhadap kecenderungan narsistik pada remaja pengguna Tiktok di Pekanbaru, dengan demikian hipotesis dalam penelitian ini diterima.